PENGELOLAAN INTERAKSI KUALITAS PROSES BELAJAR MENGAJAR TERHADAP PENGEMBANGAN DIRI ANAK DALAM KONTEKS MINAT BELAJAR - Belinda Mau; Areyne Christi (Sekolah Tinggi Teologi Excelsius, 2018)
Abstract: In this era of globalization, teachers are very dominant in self-actualizing to educate the nation in facing the challenges and competition in the world, so that they are required to improve their professionalism in dealing with any existing problems. Solutions to answer the problems faced by teachers arise in the following questions: Who is the teacher? What is the role of the teacher both as a teacher and in relation to their students? How to manage the quality of the teaching and learning process on children's self-development in the context of interest in learning? The answers are: (1) a teacher is a professional educator who educates, teaches a science, guides, trains, provides assessments, and evaluates students. (2) the role of the teacher to work holistically. The teacher not only carries out his duties as a teacher, but becomes an example and a companion to his students. (3) the teacher must be able to manage the class very well so that in every learning process, children can be interested and respond when a teacher delivers a material. Abstrak: Dalam era globalisasi ini guru sangatlah dominan di dalam mengaktualisasi diri untuk mencerdaskan bangsa dalam menghadapi tantangan dan persaingan dunia, sehingga dituntut untuk meningkatkan profesionalnya dalam menangani setiap masalah yang ada. Solusi untuk menjawab persoalan-persoalan yang di hadapi oleh guru muncul dalam pertanyaan sebagai berikut: Siapakah guru itu? Apakah peranan guru baik sebagai guru dan berhubungan dengan anak didiknya? Bagaimanakah mengelola kualitas proses belajar mengajar terhadap pengembangan diri anak dalam konteks minat belajar? Jawabnya adalah: (1) guru adalah seorang tenaga pendidik profesional yang mendidik, mengajarkan suatu ilmu, membimbing, melatih, memberikan penilaian, serta melakukan evaluasi kepada peserta didik. (2) peranan guru bekerja secara holistik. Guru tidak saja menjalankan tugasnya sebagai seorang pengajar, tetapi menjadi teladan dan teman bergaul bagi para muridnya. (3) guru harus dapat mengelola kelas dengan sangat baik sehingga dalam setiap proses pembelajaran, anak dapat tertarik dan meresponi ketika seorang guru menyampaikan sebuah materi.